THE INFLUENCE OF INTEREST, JCI, EXCHANGE RATE, ECONOMIC GROWTH, AND INFLATION ON THE PERFORMANCE OF EMPLOYEES HEALTH INVESTMENT IN BUKIT ASAM FOUNDATION - Permanasari Sembiring, Rosaidah (Dinasti Publisher, 2020)
This study aims to determine the effect of interest rates, JCI, Exchange Rate, Growth Economy and Inflation on Investment Performance Employees Health Foundation Bukit Asam. In this study, researchers used a regression method with a quantitative approach. The comparative research hypothesis is a hypothesis formulated to provide answers to the issues that are of influence. The population in this study were all of Interest Rate, JCI, Exchange Rate, Economic Growth and Inflation, and investment companies. Where the data of this study is the Interest Rate, JCI, Exchange Rate, Economic Growth and Inflation and investment company 2013 to 2017 period. The test used to test instrument this research is normality test, autocorrelation, Multicollinearity, heteroscedasticity. The results of the study that variable interest rates and a significant positive effect inverse of <0.05 and JCI positive and significant effect of <0,05 on the dependent variable, while the rupiah, Growth, and inflation is negative and not significant. While simultaneously or together there is a positive and significant influence of the independent variables on the dependent variable with a coefficient of determination of 10.1% while the remaining 89.9% is a combination of other factors not included in this study.